Investigation of the Stabilization of a Selected Expansive Soil in North Cyprus Using an Aqueous Polymer - Golhashem, Mohammadreza (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
In this research, co-polymer of Butyl Acrylate and Styrene (CBAS) is utilized to improve volume change behaviour, undrained shear strength and internal stability of a cohesive soil obtained from Famagusta Bay, Cyprus. CBAS has low viscosity improving its adsorption in the soil microstructure and its ionic structure enhances its interaction within the soil fabric. The ease of application of CBAS, by shallow mixing or direct spraying onto soils, makes it favorable for engineered fills or just to be used as a wind or water erosion measure. Treatment of the soil samples with CBAS indicated significant improvement in the shrinkage and compressibility characteristics when it is added up to 5% of dry mass of soil, whereas the swelling behaviour is improved with further addition. The secondary compression rate is reduced down to approximately a quarter of the rate obtained from untreated specimens. The unconfined compressive strength is increased significantly even at low percentages of treatment. A similar efficacy is also observed from the results of internal stability tests. The mode of the collapse of specimens in the internal stability tests changed from being `gradual cracking and slaking` to `explosive` when CBAS is used. The cyclic wetting and drying behaviour is also tested, which indicated delay in the drying periods and a reduced swelling potential for the treated specimens. Microstructural changes in the soil fabric are observed with the use of scanning electron microscopy, which indicated that an effective formation of polymer soil interaction is achieved. X-Ray Diffraction analysis and Fourier Transform Infrared Spectroscopy are performed for observation of the effect of CBAS on microstructural interactions such as electrostatic bonding and changes in soil fabric.

ÖZ: Bu araştırmada Mağusa Körfezi kıyılarında mevcut yüzeysel alüvyon tabakalarından elde edilen kohezyonlu zemin üzerinde uygulanan ‘co-polymer of Butyl Acrylate and Styrene’ (CBAS) isimli polymerin, bu zeminin hacim değiştirme, kayma dayanımı ve içsel stabilitesine olan etkisi değerlendirilmiştir. CBAS düşük viskositeli ve ionik yapısı sebebi ile hem mikroyapıya daha kolay emilimi olabilen hem de zemin içerisinde interaktivitesi yüksek bir katkı malzemesidir. Sığ zemin karıştrması veya püskürtme yötemleri ile uygulamada kolaylık sağlayabilen CBAS, mühendislik dolgularında veya sadece rüzgar ve su erozyonuna karşı koruma sağlamak için uygun bir seçenektir. Ağırlıkça %5’e kadar uygulanan CBAS katkısı, deney numunelerinin büzülme ve oturmaya karşı davranışını yüksek derecede iyileştirmesine rağmen, şişmeye karşı iyileşme bu seviyeden daha yüksek katkılarda sağlanabilmiştir. İkincil oturma hızı katkılı numunelerde dörtte bir oranında azalmıştır. Drenajsız kayma dayanımında çok düşük katkı oranlarında dahi çok yüksek seviyede iyileştirme sağlanmıştır. Buna benzer bir iyileştirme etkinliği içsel stabilite deneylerinde de elde edilmiştir. Bu deneylerde elde edilen göçme şekli ‘düzenli çatlama ve dağılma’ dan ‘ani göçme’ şekline değişmiştir. Tekrarlı ıslatma ve kurutma davranışı deneyleri katkılı numunelerde kuruma davranışını geciktirmiş ve şişme potansiyelini de azaltmıştır. Mikroyapıdaki değişimler taramalı electron mikroskopu ile gözlemlenmeye çalışılmıştır, ki bu sonuçlar efektif bir etkileşimi onaylar niteliktedir. X-ışınlı difraktometre ve Fourier Transform Infrared Spektometre deneyleri yine katkılı numunelerde mikroyapı etkileşimlerini gözlemlemek için uygulanmış ayrıca elektrostatik bağlar ve zemin yapısı incelenmiştir.
Doctor of Philosophy in Civil Engineering. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2019. Supervisor: Asst. Prof. Dr. Eriş Uygar.
Keywords: Soil Mechanics--Soils--Liquid Polymer; Aqueous polymer; Compressibility; Expansive clay; Internal stability; Stabilization; Unconfined Compressive Strength